Perlindungan terhadap Pelaku Usaha Kecil Usaha Mikro, Kecil, dan Menengah (UMKM) terhadap Persaingan Usaha Tidak Sehat - Hapsari Paramitha Wijayanti (Jurnal Hukum Lex Generalis, 2025)
Competition law is a crucial instrument in a market economy to promote fair competition and protect small businesses from monopolistic practices and unfair competition. This study examines the role of the Indonesian Competition Commission (KPPU) in safeguarding Micro, Small, and Medium Enterprises (UMKM) against the dominance of large corporations. With a Normative Juridical approach, the study showsThe findings indicate that while legal exemptions for MSMEs aim to protect them, there is a potential for abuse that requires strict monitoring. Effective enforcement of competition law is essential to create a fair business environment and promote sustainable economic growth.